Bahasa Inggris - Misbahuddin Asaad; Kharisma, Nadya Putri; Saleh, Marlin (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2024)
The sayings of the Prophet play a highly significant role as one of the two primary sources of Islam, crucial in constructing the foundation of the Islamic religion. Understanding the asbabul wurud (occasions of revelation) in hadith studies is considered equally important to comprehending the asbab an-nuzul (occasions of revelation) in the Quran, as both serve as the contextual core of an event. The study of asbabul wurud is critical in the discussion of hadiths, aiming to prevent misinterpretations of the intended meaning of a hadith. Unawareness of asbabul wurud can lead to misunderstandings, focusing solely on the textual meaning of the hadith and potentially resulting in incorrect interpretations. The research methodology employed is qualitative analysis with a library research approach. The focus of this study is on the analysis of writings discussing the asbabul wurud of a hadith. The research findings indicate that understanding the asbabul wurud of a hadith plays a crucial role in avoiding interpretative errors. The classification of asbabul wurud encompasses Quranic verses, hadiths, and related factors, such as events involving the companions. Furthermore, the study highlights the importance of understanding asbabul wurud in the context of education, emphasizing that this knowledge can contribute positively to the accurate understanding of Islamic teachings.